The Relationship Between Mother's Compliance and Consume Fe Supplementary tablets with Incidence of Anemia in Pregnant Women - Rumzi, Cindy Novita; Harahap, Juraida Roito; Fathunikmah, Fathunikmah; Susanti, Ari (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2022)
The coverage of giving blood tablets in Kuantan Singingi Regency is 54%, the district achievement target is 90%. Giving blood-added tablets is a step to prevent bleeding during pregnancy, childbirth and the puerperium. The purpose of the study was to determine the relationship between maternal compliance and how to consume blood-added tablets with the incidence of anemia in pregnant women. The research design is cross sectional with descriptive analytic research type. The study was conducted in January-May 2021 in the Working Area of ​​the Lubuk Jambi Health Center, Kuantan Singingi Regency. The population is 55 pregnant women who come to do pregnancy check-ups at the posyanti. Sampling using accidental sampling method as many as 47 pregnant women. The results of the study were processed using the Chi Square test. It showed that there was a significant relationship between maternal adherence to taking blood-added tablets (p value 0.002) and how to consume blood-added tablets (p value 0.006) with the incidence of anemia in pregnant women in the Lubuk Jambi Health Center Work Area, Kuantan Regency. Singingi. It is expected that midwives and cadres provide education and counseling to pregnant women, supervise taking medication by involving husbands and families.